Development of the revised WHOQOL-BREF Quality of Life Assessment: towards a mediation model on quality of life and post-traumatic stress - Panayiotou, Margarita (The University of Edinburgh, 2016)
The adverse consequences of posttraumatic stress on quality of life have been well documented. It is, however, possible that it is not the intrusive re-experiencing and hyperarousal posttraumatic stress symptoms that have an impact on quality of life per se, but the inflexible efforts to avoid internal experiences and emotions related to the traumatic event, and the way these emotions are expressed and experienced. Previous research shows that both experiential avoidance and emotion regulation have been found to be etiologically central to the development and maintenance of psychological problems in trauma survivors. The degree to which experiential avoidance and emotion regulation act together as toxic underlying mechanisms to explain the relationship between posttraumatic stress and quality of life is, however, yet to be examined. Quality of life is now regarded as an important outcome variable across a broad range of conditions and problem areas. The quality of life concept has generated a large body of research and yet its assessment has been a challenge for researchers. The WHOQOL-BREF is considered to be one of the few genuine quality of life measures but it has received much criticism, especially regarding the poor psychometric performance of its social relationships domain. The aim of the current thesis was twofold. The first aim involved the revision of the WHOQOL-BREF through the enhancement of the social relationships domain. In Study I 986 ill and healthy individuals from five countries worldwide completed the Pilot Revised WHOQOL-BREF (WHOQOL-BREF-R) along with measures of life satisfaction, anxiety, and depression for the detailed psychometric analysis of the scale. Study I confirmed the limitations of the social relationships domain, and despite its improvement, the performance of the overall scale was found to be poor. In fact, findings from modern and robust techniques challenged the 4-factor structure of the WHOQOL-BREF. Instead, results supported the performance of a 3-factor solution, which led to the development of a psychometrically sound measure. Study II is preceded by a systematic review of the literature investigating experiential avoidance as a mediator in trauma survivors with posttraumatic stress. Ten studies were identified and organised in two categories assessing experiential avoidance as a mediator between: 1) trauma exposure and posttraumatic stress, and 2) posttraumatic stress and maladaptive behaviours. Findings suggest that the development and maintenance of posttraumatic stress symptoms and maladaptive behaviours in the aftermath of trauma can be explained through the use of experiential avoidance. Methodological limitations and future directions for research are discussed. The WHOQOL-BREF-R was then used in Study II, which explored an integrative mediation model whereby experiential avoidance and emotion regulation were tested as mediators in the relationship between posttraumatic stress symptomatology and quality of life in trauma exposed adults. The two mediators were also explored for their overlapping relationship. A total of 360 participants from the community completed self-report measures of posttraumatic stress, experiential avoidance, emotion regulation, and quality of life. With the use of path analysis Study II found experiential avoidance and emotion regulation to be two distinct constructs that together act as an underlying mechanism explaining the impact of posttraumatic stress on quality of life. Alternative mediating models were explored. The current study makes an important contribution in the area of trauma and in the conceptualisation and assessment of quality of life. Findings can be considered as a first step towards an integrative mediation model of toxic mechanisms in trauma and quality of life. Additionally, the favourable psychometric properties of the WHOQOL-BREF-R make it a powerful tool for use in quality of life research.
Keywords: posttraumatic stress; post-traumatic stress; experiential avoidance; emotion regulation; quality of life; WHOQOL-BREF-R; scale development; mediation